TEAD2 Promotes Hepatocellular Carcinoma Development and Sorafenib Resistance via TAK1 Transcriptional Activation - Zhang, Yahui; Ren, Yidan; Dong, Guoying; Jiao, Qinlian; Guo, Nan; Gao, Ping; Li, Ya; Wang, Yunshan; Zhao, Wei (Molecular cancer research, 2024)
Hepatocellular carcinoma (HCC) is the most prevalent type of liver cancer, yet the effectiveness of treatment for patients with HCC is significantly hindered by the development of drug resistance to sorafenib. Through the application of accessibility sequencing to examine drug-resistant HCC tissues, we identified substantial alterations in chromatin accessibility in sorafenib-resistant patient-derived xenograft models. Employing multiomics data integration analysis, we confirmed that the key transcription factor TEAD2, which plays an important role in the Hippo signaling pathway, is a key factor in regulating sorafenib resistance in HCC. Functional assays illustrated that TEAD2 plays a role in promoting HCC progression and enhancing resistance to sorafenib. Mechanistically, we demonstrated that TEAD2 binds to the TAK1 promoter to modulate its expression. Furthermore, we established the involvement of TAK1 in mediating TEAD2-induced sorafenib resistance in HCC, a finding supported by the effectiveness of TAK1 inhibitors. Our research highlights that targeting the TEAD2-TAK1 axis can effectively mitigate drug resistance in patients with HCC receiving sorafenib treatment, offering a novel approach for enhancing the treatment outcomes and prognosis of individuals with HCC. Implications: Targeting the TEAD2-TAK1 axis presents a promising therapeutic strategy to overcome sorafenib resistance in HCC, potentially improving treatment outcomes and prognosis for patients.